Analisis Isi Pendidikan Karakter dalam Buku Teks “English for Nusantara” untuk Siswa Kelas Tujuh (Bilingua, 2024)
The objective of this research is to find out whether character education in the "English for Nusantara" textbook for seventh-grade students is in accordance with the current curriculum. This research analyzed character education contained in the reading and conversational texts of the textbook. The research methodology used a descriptive qualitative approach and content analysis technique. The characters found in the textbook were classified into six dimensions of the Pancasila Student Profile. The results showed that the six dimensions of the Pancasila Student Profile were found. The dimension of having faith, fear of God Almighty, having a noble character 33.2%, global diversity 12.9%, mutual cooperation 16.7%, independent 20.4%, critical reasoning 7.5%, and creative 9.3%. In the six dimensions of the Pancasila Student Profile, which have 20 elements, only 19 were found, while one element that was not found was intercultural communication and interaction. The characters in this book are mostly integrated implicitly. The primary focus dimension of the “English for the Nusantara” textbook was having faith, fear of God Almighty, and having noble character. In addition, the main focus element in this textbook was the manner towards others. Based on the classification of character education stated by Prismarani (2014), this textbook scored 95% and was classified as ‘very high’ quality.